Mitigação do Risco da alta volatilidade dos preços da energia elétrica no mercado australiano - Lyra, Marcos da Silva (2005)
This dissertation presents a study of the characteristics and behavior of the electricity prices in the free electricity power market. Models for spot price simulation as well as for option pricing are analyzed. Those options are used for hedging the risk of the high volatility in electricity prices. This research has the objective of analyzing the characteristics of electricity price in the power market, obtain the parameters to calibrate a simulator and propose derivative tools for hedging contracts. An evaluation of this study, shows that due to particularities in the electricity prices, it is necessary to use models with a more complex pricing process, which can capture the peculiarity of the electricity prices. Based on it, an excel worksheet using the mean reversion jump diffusion model was built. Those worksheets are able to extract the parameters of the electricity price, calibrate the model, simulate the behavior of the prices in the power market, pricing options and simulate results in several scenarios. To accomplish it, a combination of option price, amount of energy protection and strike price where used. The simulator uses the regime switching model with two regimes (mean reversion regime and the jump regime) for shape the behavior of the electricity prices, as well as for pricing a call option. The objective of the simulation is to find a strike price, an option premium and a volume of energy to be contracted that minimize the costs with electricity purchase and maximize the return. The result of the simulations showed that the probability to obtain positives scenarios (lower costs with electricity purchase) with the use of call options is much higher than without them. Based on it the use of derivative for risk minimization in the free electricity power market becomes essential for all the agents in this sector. The Brazilian electricity power market is still far from this model, due to the fact that the contracts are signed for a long term period, where the volume of energy and its price are already determined. Besides the rules for this market is still being reviewed, causing uncertainty and low interest for new investors.